Variations in 0° and 8° Caudal Angulation in Lumbosacral Joint Lateral Projection Examinations with Clinical Low Back Pain to Show More Informative Anatomy in the Radiology Department of Pariaman Regional General Hospital - Mareta, Santa; Sari, Oktavia Puspita; Dewilza, Nerifa; Nansih, Livia Ade; Giani, Nadhifa Shofikha (Oshada, 2025)
This quantitative experimental study, conducted at the Radiology Department of Pariaman Regional General Hospital, compared the diagnostic quality of lateral lumbosacral radiographs using 0° and 8° caudal beam angles. With a sample of three female patients assessed by five radiology specialists, results analyzed via the Wilcoxon test showed the 8° caudal projection (score: 3.87) was superior to the 0° angle (score: 3.07). The 8° angle provided a more optimal image, characterized by a well-opened intervertebral disc space and clear visualization of the spinous process without sacral overlap, making it more informative for clinical evaluation. In contrast, the 0° angle, while offering a clearer vertebral body outline, resulted in a less open disc and superimposed spinous process. The findings suggest that an 8° caudal beam angle enhances visualization of key anatomical structures in lateral lumbosacral radiography.